2003
DOI: 10.1161/01.atv.0000054198.68894.88
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RhoA/Rho Kinase Signaling in VEGF-Induced Endothelial Cell Migration and Angiogenesis In Vitro

Abstract: Objective— Growth factor-induced angiogenesis involves migration of endothelial cells (ECs) into perivascular areas and requires active remodeling of the endothelial F-actin cytoskeleton. The small GTPase RhoA previously has been implicated in vascular endothelial growth factor (VEGF)-induced signaling pathways, but its role has not been clarified. Methods and Results— VEGF induced the activation of RhoA and recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
224
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(244 citation statements)
references
References 59 publications
17
224
1
2
Order By: Relevance
“…We found that RhoA transiently becomes activated 5-15 min after VEGF treatment. This data confirmed work by other groups [18,19] that demonstrated a rapid and transient increase of RhoA activity in the first few minutes after VEGF treatment. Cdc42 was also activated 5-15 min after stimulation with VEGF; this activity declined and elevated again around 60 min.…”
Section: Vegf Activates Rac1 Through Vegfr-2 In Endothelial Cellssupporting
confidence: 92%
“…We found that RhoA transiently becomes activated 5-15 min after VEGF treatment. This data confirmed work by other groups [18,19] that demonstrated a rapid and transient increase of RhoA activity in the first few minutes after VEGF treatment. Cdc42 was also activated 5-15 min after stimulation with VEGF; this activity declined and elevated again around 60 min.…”
Section: Vegf Activates Rac1 Through Vegfr-2 In Endothelial Cellssupporting
confidence: 92%
“…In addition, as a major angiogenesis factor, in VEGF-stimulated cells, RhoA signaling is necessary for cell migration (25). Previous experiments indicated that RhoA critically regulates angiogenesis driven by VEGF and constitutively active RhoA can complement VEGF to increase angiogenesis by >100%, whereas dominant negative RhoA markedly inhibits VEGF-driven neovascularization (26). However, in this study, we demonstrate that the overexpression of RhoA is sufficient to induce migration and increase motility of human umbilical vein endothelial cells, in the absence of any exogenous stimulation, such as growth factors or cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been demonstrated that VEGF increases RhoA activity along with its recruitment to the cell membrane; at the same time, RhoA signaling has been implicated in VEGF-mediated angiogenesis. 8 In addition, RhoA activation increases tyrosine phosphorylation of VEGF receptor 2 (VEGFR-2). 9 Although RhoA signaling has been implicated in the regulation of angiogenesis, a comprehensive analysis of the specific mechanisms by which it mediates VEGF-induced angiogenesis still needs to be done.…”
Section: Introductionmentioning
confidence: 99%